Detection of E. coli O157:H7 in wild life from disturbed habitats in Sarawak, Malaysia - Kasing, Apun; Kho, Khai Ling; Chong, Yee Ling; Hashimatul Fatma, Hashim; Abdullah, M. Taj; Rahman, M.A; Lesley Maurice, Bilung; Samuel, Lihan (Academic Journals Inc., 2011)
This study was carried out to assess the occurrence of Escherichia coli and to detect the pathogenic strain Escherichia coli O157:H7 in birds, bats and rodents from disturbed habitats comprising of two urban forests and an oil palm plantation habitats located along the Rejang Basin, Sibu in the state of Sarawak, using both standard microbiological and molecular techniques. A total of 105 bird hosts, 44 of rodent hosts and 84 bat hosts represented 48 species of birds, one species of rodent and ten species of bats were screened for the presence of Escherichia coli. The representative isolates were cultured on a highly selective agar, Cefaxime-tellurite sorbitol MacConkey agar for the detection of Escherichia coli O157:H7. From the microbiological analysis, the overall occurrences of Escherichia coli in the hosts were 43% in rodents, 18% in birds and 11% in bats. The isolates were tested for the presence of pathogenic Escherichia coli O157:H7 strain by multiplex PCR method targeting the slt-I, slt-II, rfbE and fliCH7 genes. The slt-I, slt-II, rfbE genes were not detected in any of the E. coli isolates. This study indicated that bats, birds, or rodents from these habitats in Sarawak did not serve as an important reservoir of Escherichia coli O157:H7 and thus were of no risk in the epidemiologic cycle of emerging enteric bacterial zoonoses in the state of Sarawak, Malaysia.